(untitled) (Research, Society and Development, 2022)
Objective: To compare the prevalence of radix in the mandibular first and second molars using cone beam computed tomography and panoramic radiography. Methods: 850 exams were analyzed, dated from January 2017 to February 2021, in a radiology clinic in the city of Brumado-Ba. Images were acquired using a Cranex 3D CT scanner. Thus, a total of 280 lower first and second molars were selected by tomographic images and then the images of the relative panoramic radiographs were separated. Radix prevalence was analyzed using On Demand software for the scans from CT and Scanora software for the panoramic radiographs. The data obtained were analyzed using descriptive and inferential statistics, using methods to compare between variables and methods of interest. A significance level of 5% was assumed for all analyzes. Results: No case of radix was identified in the analysis of panoramic radiograph images, corresponding to a percentage of 0%. In tomographic sections, this study showed that the prevalence of radix was 0.7%, 100% of which was radix entomolres. There was no statistically significant difference in the prevalence of these canals with respect to age group, sex, and group of teeth examined (first or lower second molars). Conclusion: It was concluded that CBCT is an important auxiliary method in the analysis of the presence of radix canals.